Potensi air tanah di cekungan air tanah Sambas, Provinsi Kalimantan Barat - Hidayat, Robi S. (Indonesian Journal on Geoscience, 2008)
http://dx.doi.org/10.17014/ijog.vol3no4.20083The grouping of the groundwater potential of Sambas area using the quantity and quality matrix of those groundwater can be divided into three classes. First, high groundwater potential area distributed in the Jawai, Teluk Keramat, Sejangkung, and Sakura Sub-regencies. Second, the moderate groundwater potential area covers the Sambas and Tebas Sub-regencies. Third, the low groundwater potential area cov- ers the Sanggauledo and SeluasÂ  Sub-regencies. Â